2021
DOI: 10.1021/acs.chemrev.1c00165
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry, Functionalization, and Applications of Recent Monoelemental Two-Dimensional Materials and Their Heterostructures

Abstract: The past decades have witnessed a rapid expansion in investigations of twodimensional (2D) monoelemental materials (Xenes), which are promising materials in various fields, including applications in optoelectronic devices, biomedicine, catalysis, and energy storage. Apart from graphene and phosphorene, recently emerging 2D Xenes, specifically graphdiyne, borophene, arsenene, antimonene, bismuthene, and tellurene, have attracted considerable interest due to their unique optical, electrical, and catalytic proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
83
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(83 citation statements)
references
References 432 publications
(1,020 reference statements)
0
83
0
Order By: Relevance
“…[19][20][21][22][23][24][25][26][27] In addition, with unique optical, electrical, and catalytic properties, 2D transition metal carbides have attracted considerable interest and succeeded in a broader range of intriguing applications such as optical devices, optoelectronics, catalysis, biomedicine, and energy storage. [28][29][30][31] Very recently, the outstanding SERS performance of transition metal carbides has been discovered. 19,[32][33][34] For instance, Du et al reported that Mo 2 C and MoN hollow spheres with large surface areas displayed strong surface-enhanced Raman effects.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26][27] In addition, with unique optical, electrical, and catalytic properties, 2D transition metal carbides have attracted considerable interest and succeeded in a broader range of intriguing applications such as optical devices, optoelectronics, catalysis, biomedicine, and energy storage. [28][29][30][31] Very recently, the outstanding SERS performance of transition metal carbides has been discovered. 19,[32][33][34] For instance, Du et al reported that Mo 2 C and MoN hollow spheres with large surface areas displayed strong surface-enhanced Raman effects.…”
Section: Introductionmentioning
confidence: 99%
“…Two dimensional (2D) materials have become a research hot spot in recent years because of their novel and attractive properties, offering promising basics for designing all kinds of nanoelectronic and photoelectronic devices. [ 1–5 ] Until now, various 2D materials have been fabricated in experiments or predicted theoretically, but each material exhibits its own complement of favorable and unfavorable natures. [ 5–8 ] For example, although graphene has very high carrier mobility, its zero band gap limits the application in optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1–5 ] Until now, various 2D materials have been fabricated in experiments or predicted theoretically, but each material exhibits its own complement of favorable and unfavorable natures. [ 5–8 ] For example, although graphene has very high carrier mobility, its zero band gap limits the application in optoelectronic devices. [ 6 ] Although MoS 2 possesses high on‐off current ratio and extended band gap, its carrier mobility is relatively low.…”
Section: Introductionmentioning
confidence: 99%
“…48 A recently reported concept, two-dimensional (2D) monoelemental materials, Xenes has advanced into the development of inorganic and organic nanostructures for imaging, sensing and targeted delivery of therapeutics for biomedical applications. 49 Xenes have already shown promise for various biomedical applications. The scope of biomedical applications can be further expanded by making the best of the optical properties, induced magnetic characteristic of Xenes, and rational surface modification with drugs, photosensitizers, imaging, and sensing agents.…”
Section: Discussionmentioning
confidence: 99%